Hierarchy and subsurface correlation of muddy baffles in lacustrine delta fronts: a case study in the X Oilfield, Subei Basin, China - Kun Qi (KeAi Communications Co., Ltd., 2018)
Abstract Muddy baffles are one of the major geological factors controlling the underground fluid flow as well as the remaining oil distribution. This study used detailed drilling data from the E1 f 1 reservoir in the X Oilfield, Subei Basin, China, to investigate the hierarchical muddy baffles developed on lacustrine delta fronts and their precise cross-well correlation. According to the theories on allogenic and autogenic cycles as well as the genesis and scales of muddy baffles, five orders of muddy baffles were classified, which provided various degrees of difficulty when attempting interwell correlation. Under the guidance of a reliable stratigraphic model, the precise cross-well correlation of muddy baffles could be achieved and the key point of establishment of this stratigraphic model was to calculate foreset angles of hierarchical muddy baffles during deposition. During calculation, the relationships between sediment flow direction, higher-order strata dipping direction, well types and well trajectory direction should all be taken into consideration and some other angles (referred to here as θ 1, θ 2 and θ 3) should also be measured. Such new methods of cross-well correlation for hierarchical muddy baffles could greatly reduce the uncertainties and multiple solutions, which in turn would be significant for efficient development and oil recovery enhancement in the reservoirs.